2013
DOI: 10.3109/00016489.2013.805341
|View full text |Cite
|
Sign up to set email alerts
|

Conservation surgery for hypopharyngeal cancer: changing paradigm from open to endoscopic

Abstract: Patients who underwent ELM demonstrated a shorter decannulation period (7 vs 11 days, p = 0.010), time using a nasogastric tube (7 vs 16 days, p = 0.043), and hospitalization stay (12 vs 22 days, p = 0.0061) than those who underwent OPLP. The 3-year overall and disease-specific survival rates were comparable between ELM and OPLP (79% vs 64%, p = 0.151, and 83% vs 71%, p = 0.320, respectively). The ELM patients had better laryngeal preservation (92% vs 71%, p = 0.048). The number of OPLPs performed has decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
26
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 20 publications
4
26
0
1
Order By: Relevance
“…In the present study, there were no major complications, such as perioperative massive bleeding, pharyngocutaneous fistula formation, or airway compromise. The average hospital stay after surgery was 10.3 days, which was similar to 12 days of TLM reported by Kuo et al…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the present study, there were no major complications, such as perioperative massive bleeding, pharyngocutaneous fistula formation, or airway compromise. The average hospital stay after surgery was 10.3 days, which was similar to 12 days of TLM reported by Kuo et al…”
Section: Discussionsupporting
confidence: 82%
“…Our experience of 10 cases indicates that TORS without the tracheostomy procedure can be successfully executed with en bloc resection of the early pyriform sinus tumor, as in some TLM cases. Our patients' endotracheal tubes were removed 1.2 days (average) after TORS, which was comparable to 7 days after TLM, as reported by Kuo et al However, TORS offers several advantages, such as the excellent panoramic view of the hypopharynx that ensures an en bloc cone‐shaped excision of the pyriform sinus (see Figure ) that is usually difficult in TLM. The endowristed instrument of TORS has 7 degrees of freedom that allow a precise incision and dissection at different angles/directions with motion scaling and tremor reduction function that avoids paradoxical long instrument movement in TLM.…”
Section: Discussionsupporting
confidence: 82%
“…The previous studies reported that the LRC rate of early-stage HPSCC was 60% to 88% when treated either by surgery [5-7] or by definitive RT [8-13]. We found that the 5-year LRC rate of these patients was 65%, which was comparable to other studies.…”
Section: Discussionsupporting
confidence: 86%
“…Among the 33 patients, LRF occurred in 13 patients: 8 had LF, 1 had RF, and 3 had combined failures. Kuo et al [7] reported 53 patients treated with either open partial laryngopharyngectomy or endoscopic laser microsurgery had a 5-year LRC of 71%. Of the 53 patients, 13 experienced failures (8 LF and 5 RF).…”
Section: Discussionmentioning
confidence: 99%
“…This makes it premature to infer a causal link between GERD and HNCs in either direction, or whether a confounding factor might account for both findings. Nevertheless, smoking and alcohol are risk factors for GERD as well as for HNCs [23,24]; therefore, the association can likely be explained by the fact that those who smoke and drink have GERD as well as other risk factors associated with HNCs. The relationship between GERD and HNCs is more pronounced among men, and smoking and alcohol are more common among men than among women; therefore, these carcinogens can still be considered contributing factors [25,26].…”
Section: Discussionmentioning
confidence: 95%